Axenic cultivation of Pleurotus ostreatus Var. Florida in supplemented sugarcane bagasse briquettes - Magalhães, Anderson C. [UNESP] (2018)
Articles on the applicability of briquetting to the production of mushrooms are rare. Therefore, this research provides the scientific community and, mainly, producers, unpublished technical information regarding the productive yield of oyster mushroom cultivated in sugarcane bagasse briquettes supplemented with bioproducts of cereals. In 30 days of axenic cultivation, 6 tons-force briquettes with 80% humidity resulted in higher productivity (30.4%), and generated the lowest physical volume of exhausted compound (44.8%), thus, overcoming the technical performance of the other briquetting matrices tested, and even of methods traditionally used for the preparation of substrate for P. ostreatus cultivation on a commercial scale. The conclusion is, therefore, that the axenic cultivation of P. ostreatus var. Florida in sugarcane bagasse briquettes, supplemented with bioproducts of cereals, has technically qualified as an original and efficient method for the production of high biological value protein by the recycling of agricultural residues and can therefore guarantee multiple economic benefits to the agribusiness of the oyster mushroom, in addition to allowing reduction of environmental impacts by the restricted generation of exhausted compound in the post-harvest stage.